P225 What is the current provision of service for gastrostomy insertion in England?. (19th June 2022) - Parr, Heather; Williams, Elizabeth A; White, Sean; Hopper, Andrew D; McAlindon, Mark E; Thompson, Nick; McKinlay, Alastair; Sanders, David S
Abstract : Introduction: Significant morbidity and mortality can be associated with gastrostomy insertion, likely influenced by patient selection, indication and aftercare. We aimed to establish what current variation in practice exists in England and how this has improved by comparison to our previously published British Society of Gastroenterology (BSG) survey of 2010. Methods: We approached all NHS hospitals in England (n = 198). Email and web-based questionnaires were circulated. This data was compared with the National endoscopy database (NED) (2019 and 2020) and the 2010 BSG survey. Results: The response rate was 69% (n = 136/198). Estimated PEG placements in the UK are currently 6, 500 versus 17, 000 in 2010 (P <0.01). There is a dedicated PEG consultant involved in 59% of the centres versus 30% in 2010 (P < 0.0001). Multidisciplinary team meeting (MDT) discussion on gastrostomy insertion occurs in 66% versus 40% in 2010 (P < 0.05). Formal aftercare provision occurs in 83% versus 64% in 2010 (P < 0.001). 74/107 respondents (69%) reported feeling pressurised to authorise a gastrostomy. Most often from other specialty teams and family members. Conclusions: This national survey, validated by the results from NED, demonstrates a reduction of over 60% for PEG insertion rates compared to previous estimates. There has also been an increase in consultant involvement, MDT discussion and aftercare provision. However, two-thirds of responders described 'pressure' to insert a gastrostomy. Perhaps further efforts are needed to include or educate other specialty teams, patients and next of kin.